2002
DOI: 10.1046/j.1524-475x.2002.10803.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of glutathione redox dysfunction in diabetic wounds

Abstract: We propose that diabetic foot ulcers and diabetic mouse wounds have insufficient glutathione to maintain correct cellular redox potential. Therefore, tissue samples from the wound edge of diabetic foot ulcers, diabetic mice wounds and nondiabetic mice wounds were obtained. Levels of glutathione, cysteine, and mixed protein disulfide were determined and topical application of esterified glutathione in carboxymethylcellulose or carboxymethylcellulose alone was applied to the mice wounds. Diabetic foot ulcer mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 24 publications
(26 reference statements)
3
26
0
1
Order By: Relevance
“…Whereas, the profuse ROS not only damage extracellular structure proteins, lipids, and DNA but also stimulate signal transduction pathways to prolong the inflammatory phase of wound healing. Many scientific publications have proven the beneficial effect of different plant-based antioxidants on wound repair process [24, 25] and our findings of free radical scavenging activity (DPPH, SRSA, FRAP, and FCR) in methanol and water I. coccinea extracts revealed that this plant may be useful in wound healing (Figure 1 and Table 2). …”
Section: Discussionsupporting
confidence: 53%
“…Whereas, the profuse ROS not only damage extracellular structure proteins, lipids, and DNA but also stimulate signal transduction pathways to prolong the inflammatory phase of wound healing. Many scientific publications have proven the beneficial effect of different plant-based antioxidants on wound repair process [24, 25] and our findings of free radical scavenging activity (DPPH, SRSA, FRAP, and FCR) in methanol and water I. coccinea extracts revealed that this plant may be useful in wound healing (Figure 1 and Table 2). …”
Section: Discussionsupporting
confidence: 53%
“…In contrast, lower levels of antioxidants ( e.g. glutathione) were associated with improper wound healing (207,256). …”
Section: Redox Control Of the Cell Cycle And Proliferative Disordersmentioning
confidence: 99%
“…Our previous study demonstrated that cutaneous gene therapy of manganese superoxide dismutase or overexpressing GTP cyclohydrolase I to retard NOS uncoupling was able to restore the delayed diabetic wound healing with suppression of wound O 2 · − as well as a concomitant augmentation of NO levels [8,9]. Accordingly, studies have shown that antioxidants accelerate diabetic wound healing due to enhanced NO bioavailability [10,11].…”
Section: Introductionmentioning
confidence: 99%